MAKNA KATA JANCUK DALAM FILM LARA ATI: Analisis Semiotika Roland Barthes - Ja'far Shadiq, Husayn; Riyanto, Buddy; Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research aims to reveal the meaning of the word jancuk in the film Lara Ati by Bayu Skak through Roland Barthes' semiotic analysis. The word jancuk in the context of this film is often used as an informal term and has different connotations depending on the context. The data collection technique is in the form of documentation, namely using scenes in the film Lara Ati which show the use of the word jancuk. The research results show that the word jancuk in the film Lara Ati not only functions as a curse, but also as a greeting and a symbol of closeness in friendships. Roland Barthes' semiotic analysis helps understand how the word jancuk becomes a complex sign, containing diverse and changing meanings depending on the context. Thus, this research contributes to a deeper understanding of how symbols in the media can provide complex and varied meanings, as well as how semiotic analysis can be used to reveal these meanings. Keywords: Jancuk, Film Lara Ati, Semiotics, Roland Barthes